Case Report: Pregnancy with Fetal Hydrathorax - Putra, Aditya Arya; Wicaksono, Rahmad Rizal Budi; Pramono, M. Besari Adi; Rini, Arsita Eka (Diponegoro International Medical Journal, 2021)
Background: Cases of fetal hydrothorax (FHT) are rare, with an occurrence probability of 1 in every 10,000-15,000 pregnancies. The condition may remain undiagnosed, and the fetus may be aborted, or death may occur soon after birth in outlying hospitals before transfer to a tertiary care center. The incidence rate of FHT is higher in males than females (2:1). One of the most effective methods of diagnosing fetal hydrothorax is sonography. Three forms of currently available treatments are: thoracentesis, thoracoamniotic shunting (TAS), and thoracomaternal cutaneous drainage. Fetal outcomes could be improved by performing the Extrauterine Intrapartum Treatment (EXIT) procedure.Case Presentation: We present two cases of first pregnancy primary FHT. In the first case, a 24-year-old woman was diagnosed with asymptomatic FHT in the 28th week of gestation without any prior history. In the second case, a 22-year-old woman with poor medical history was diagnosed in the 35th week of pregnancy and was experienced difficulty of breathing. Both pregnancies were delivered by cesarean section based on obstetric indications. Thoracentesis was performed on both neonates, and pathological examination of the pleural fluid was conducted. However, they died shortly after birth.Conclusion: The EXIT procedure is still a challenging method. A fetus with FHT is at significant risk of pulmonary hypoplasia and respiratory distress following delivery. Early diagnosis and intervention of FHT are vital to ensure a good prognosis. Approaching multidisciplinary groups, providing supportive diagnostic facilities and financial support is essential in improving fetal outcomes and preventing FHT in subsequent pregnancies.